Nutritional characterization of some major edible insects around Wukari, Taraba state, Nigeria - Emmanuel, Okrikata; Itohan, Otabor Jane; Oyewole, Ogunmola Adeniyi (International Research Journal of Insect Sciences, 2023)
Many people go for edible insects in sub-saharan Africa in order combat hunger and to satisfy appetite. Though, generally known as good source of proteins; if insects contain antinutrients in disproportionate levels, they can pose health risk to humans. This study therefore analysed the nutritional and antinutritional components of some insects commonly consumed around Wukari, Nigeria: Shea caterpillar – Cirina butyrospermi Vuillet (Lepidoptera: Saturniidae), Termite – Macrotermes bellicosus Smeathman (Isoptera: Termitidae), Cricket – Gryllus bimaculatus De Geer (Orthoptera: Gryllidae) and Grasshopper - Zonocerus variegatus (Orthoptera: Pyrgomorphidae) vis-à-vis African catfish – Clarias gariepinus Burchel (Siluriformes: Clariidae) which served as control. Proximate, mineral and the antinutrient component were analysed using standard procedures. Results revealed that grasshoppers had more moisture, fat and carbohydrate content than catfish. Also, cricket had an appreciable amount of protein, ash, and fibre content. However, the highest protein content was found in cricket, while grasshoppers contained the least protein. The mineral content analysis revealed that cricket had the highest calcium, magnesium, potassium, sodium and zinc content which differed significantly from catfish. The antinutrient analysis revealed that the least amount of tannins was in grasshoppers and phytates, in crickets. The amounts of antinutrients found in the insect samples are largely comparable to that in catfish. The insects assayed are healthy for human consumption and could serve as nutritional supplements. These findings revealed that the assayed insects contain high nutritional components which can substitute catfish in diets in the communities around the study area, and perhaps, beyond.